Creating sustainable networks to enhance women's participation in higher education in Papua New Guinea. Issue 2 (4th March 2022) - Aisoli-Orake, Rachel; Bue, Veronica; Aisi, Mary; Ambelye, Imelda; Betasolo, Mirzi; Nuru, Tindi; Kialo, Dora; Akanda, Shamsul; Denano, Sogoing; Yalambing, Lydia; Gasson, Susan; Spencer, Elizabeth; et al.
ABSTRACT: The challenges of raising the participation of women as leaders in higher education globally have been extensively but unevenly documented. Potential has been identified for international developmental networks to support an increasing presence of women as leaders in emerging higher education systems. Through an exploration of shared experiences and learnings in a specific developmental network of women, and some men, from universities in Papua New Guinea and Australia, the wider implications of local challenges became visible. A Collaborative Research Culture Framework has been used to highlight key collaborative principles that enable and enhance women's participation in higher education. The authors have framed their theoretical exploration of the issues informed by their own experiences of collaborating to overcome challenges faced by women participating in higher education.